Optimizing the nordic hamstring exercise: Effects of shin position on knee flexor torque and muscle activity - Kmetic, K.; Spudic, D. (International Journal of Athletic Therapy & Training, 2025)
The Nordic Hamstring Exercise (NHE) is widely regarded for its effectiveness in enhancing eccentric strength and reducing the risk of injuries, particularly in field sports and sprinting activities. This study explores the impact of varying shin angle positions on knee flexion torque and muscle activation during the NHE. Fifteen male participants with a background in strength training participated in a cross-sectional study, performing three NHE variations: inclined, horizontal, and declined shin positions. Key variables analyzed included peak torque, peak activation of the knee flexor muscles, and the angles at which these peaks occurred across all variations. A repeated-measures analysis of variance revealed that the declined NHE, where the knees were positioned higher than the ankles, produced the highest peak torque at more extended knee angle positions. These torque angles corresponded to the greatest activation of the knee flexor muscles. The results indicate that the declined shin position during the NHE most closely replicates the mechanical demands and activation of the knee flexors observed during the late swing phase of sprinting—a critical phase for optimizing performance and minimizing the risk of hamstring injuries.